2-Hydroxy-4-methoxybenzaldehyde (HMB) disrupts ergosterol biosynthesis, redox metabolism, and DON biosynthesis of Fusarium graminearum revealed by transcriptome analysis - Xiao, Hongying; Zhang, Yiming; Li, Qian (Frontiers in Microbiology, 2025)
The phytopathogenic fungus Fusarium graminearum causes Fusarium head blight, which threatens agricultural yield and human health. We previously demonstrated that a plant-derived natural compound, 2-hydroxy-4-methoxybenzaldehyde (HMB), can inhibit F. graminearum. This study continued to investigate its antifungal mechanism. Compared to the control, HMB treatment at the minimum inhibitory concentration (MIC) significantly reduced ergosterol levels by 61.78%, indicating compromised fungal membrane integrity. Concurrently, intracellular reactive oxygen species (ROS) levels increased 22-fold, accompanied by a 146.03% increase in hydrogen peroxide (H₂O₂) content. Meanwhile, superoxide dismutase (SOD) activity increased, while catalase (CAT) activity declined, suggesting a marked change of redox metabolism upon HMB exposure. In addition, Quantitative Real-time PCR (qRT-PCR) analysis revealed that HMB treatment significantly regulated the expression of genes participating in ergosterol biosynthesis (Erg2, Erg5, Erg6, etc.), DON biosynthesis (up to 16 genes), the redox system (MnSOD, Cu/ZnSOD, GSS, and CAT), global regulators (LaeA, VeA, and VelB), and stress signaling pathways (Hog1, Ssk1, Ssk2, and Pbs2). These findings revealed the in-depth antifungal mechanism of HMB and proposed that HMB holds potential as an antifungal agent.